Trigo Candeal: Influencia genotipo ambiente en rendimiento y calidad - Larsen, Adelina Olga; Jensen, Carlos Alberto; Molfese, Elena Rosa; Astiz, Valentina; Seghezzo, Maria Laura (Universidad Nacional del Noroeste de la Provincia de Buenos Aires (UNNOBA), 2025)
Póster de la Presentación